2017
DOI: 10.1111/aman.12929
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Safety: Characterizing Fieldwork Experiences and Their Implications for Career Trajectories

Abstract: Numerous studies use quantitative measures to evaluate retention, advancement, and success in academic settings. Such approaches, however, present challenges for evaluating the lived experiences of academics.Here, we present a qualitative thematic analysis of self-reports of positive and negative experiences that occurred while conducting academic field research. Twenty-six semistructured interviews highlighted two central themes:(1) variability in clarity of appropriate professional behavior and rules at fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
173
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(174 citation statements)
references
References 75 publications
1
173
0
Order By: Relevance
“…These inequities apply as much to fieldwork as to campus life. Recently, two SAFE (Survey of Academic Field Experiences) studies within anthropology documented a high level of sexual harassment in field settings [6,49], a finding that has been replicated in other sciences [5]. These lines of investigation also highlight the lack of awareness among those with privilege that their tolerance of structural impediments imposes silence on those with less power [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These inequities apply as much to fieldwork as to campus life. Recently, two SAFE (Survey of Academic Field Experiences) studies within anthropology documented a high level of sexual harassment in field settings [6,49], a finding that has been replicated in other sciences [5]. These lines of investigation also highlight the lack of awareness among those with privilege that their tolerance of structural impediments imposes silence on those with less power [49].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two SAFE (Survey of Academic Field Experiences) studies within anthropology documented a high level of sexual harassment in field settings [6,49], a finding that has been replicated in other sciences [5]. These lines of investigation also highlight the lack of awareness among those with privilege that their tolerance of structural impediments imposes silence on those with less power [49]. In all these studies of discrimination and harassment, respondents felt that speaking out would jeopardize their careers in ways white men rarely experience [5,6,49,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When these acts occurred, the victims were more likely to be women, and either junior colleagues or students. The impact of these attacks may be long-lasting: Kathryn Clancy and co-authors posited that the strain and stress of experiencing harassment and assault may contribute to the 'leaky pipeline' phenomenon 1 , that is, the gradual loss of women from science, technology, engineering and mathematics fields; their 2017 follow-up study 2 confirmed this perception among victims of historic harassment.…”
mentioning
confidence: 99%
“…The 2017 study highlights the difficulty of establishing acceptable behavioural norms in the absence of explicit and enforced policy, as well as the overwhelming importance of such policies in fieldwork contexts: where codes of conduct and expectations were not clearly established, understood and enforced, there was a correlation with higher rates of sexual harassment 2 . It seems probable, although not tested in that particular study, that a correlation would exist with other forms of bullying and abuse as well.…”
mentioning
confidence: 99%